ï¿¼MOTIVATION AND CONFIDENCE ï¿¼OF INDONESIAN TEACHERS ï¿¼TO USE ENGLISH AS A MEDIUM OF INSTRUCTION - Mangasa Aritonang (TEFLIN Journal, 2014)
This research paper investigates the motivation and confidence of Indonesian teachers of non-English to learn English and to use it as a medium of instruction resulting from their participation in a blended learning course. The purpose of the English learning for this particular group of teachers was to enable them to create English-speaking teaching and learning environment. Such environment is perceived as necessary to enhance English language learning and acquisition in some Indonesian vocational schools. The levels of motivation and confidence have been an issue because they potentially either contribute to or hinder English language learners to learn and use English for interactions. This qualitative research was undertaken using an interpretive research paradigm and a case study approach. Qualitative research data were collected from multiple sources such as in-depth interviews, observation notes, online interaction script, and reflective journals of the participants. Quantitative data were collected through surveys to add meaning to the qualitative data. The research revealed varying increase in the levels of motivation and confidence of the participants. Transformation of extrinsic to intrinsic motivations appeared to occur. Contributing factors to the increase of the motivation and confidence are discussed in this paper.Â